Prefabricated elements and their advantages in the physical-financial schedule (Research, Society and Development, 2022)
Prefabricated elements arrive in Brazil as an innovation for civil construction. Still not widespread, they bring advantages in the physical and financial schedule of the work in projects with many floors and with a short term. The industrialization of civil construction has been increasing the series production of kitchens and bathrooms, which are the most used. The bathrooms are manufactured on an industrial production line and arrive ready for work, respecting the project's architecture and customer specifications, simply placing them in the previously planned area and connecting them to the water, sewage and energy networks. In this way, all steps of material control, finishing, installation execution and quality control are carried out at the factory. Coatings, hydraulic and electrical installations and all accessories are installed on the assembly line, thus avoiding rework and waste of materials during the work. Once completed, the finished (or pre-fabricated) bathrooms are inspected and checked by quality control at the various stages: tightness, flow, trim, pressure and electrical circuits. It has several advantages in its use, such as a reduction in labor, reduction in the construction schedule, among others. This article aims to analyze the technical and economic feasibility of Ready-To-Eat Bathrooms and evaluate the deadlines for the execution of prefabricated and conventional methods through a case study. It is imperative that this system be applied in large projects that have a short schedule and with the possibility of fines in case of delay, as they are more expensive than conventional bathrooms.